Endothelial cilia dysfunction in pathogenesis of hereditary hemorrhagic telangiectasia - Eisa-Beygi, Shahram; Burrows, Patricia E.; Link, Brian A. (Frontiers in Cell and Developmental Biology, 2022)
Hereditary hemorrhagic telangiectasia (HHT) is associated with defective capillary network, leading to dilated superficial vessels and arteriovenous malformations (AVMs) in which arteries connect directly to the veins. Loss or haploinsufficiency of components of TGF-β signaling, ALK1, ENG, SMAD4, and BMP9, have been implicated in the pathogenesis AVMs. Emerging evidence suggests that the inability of endothelial cells to detect, transduce and respond to blood flow, during early development, is an underpinning of AVM pathogenesis. Therefore, components of endothelial flow detection may be instrumental in potentiating TGF-β signaling in perfused blood vessels. Here, we argue that endothelial cilium, a microtubule-based and flow-sensitive organelle, serves as a signaling hub by coupling early flow detection with potentiation of the canonical TGF-β signaling in nascent endothelial cells. Emerging evidence from animal models suggest a role for primary cilia in mediating vascular development. We reason, on recent observations, that endothelial cilia are crucial for vascular development and that embryonic loss of endothelial cilia will curtail TGF-β signaling, leading to associated defects in arteriovenous development and impaired vascular stability. Loss or dysfunction of endothelial primary cilia may be implicated in the genesis of AVMs due, in part, to inhibition of ALK1/SMAD4 signaling. We speculate that AVMs constitute part of the increasing spectrum of ciliopathy-associated vascular defects.